Improving the Efficiency of Multimedia Learning and the Quality of Experience by Reducing Cognitive Load - Miloš Ljubojević; Mihajlo Savić; Danijel Mijić; Grujica Vico (Applied Sciences)
The design of multimedia teaching materials and the principles of their presentation to students strongly influence distance learning efficiency. The appropriate design of online educational multimedia content became especially important during the period of the COVID-19 crisis. This study presents a methodology for improving the efficiency of multimedia-based distance learning by reducing the cognitive load. Combining the segmentation principle with pauses and testing questions in the design of multimedia teaching materials has a positive influence on reducing the cognitive load in distance learning. Practice as an instructional element was more efficient if it was used between the multimedia educational segments than after the presentation of complete multimedia material. The obtained experimental results show an improvement in distance learning efficiency and an increase in the students’ quality of experience. The improvement of learning outcomes using the proposed methodology of multimedia segmentation combined with pauses and testing questions can be especially important for distance education in situations such as the COVID-19 pandemic.